Estudo comparativo entre diversos revestimentos para pisos quanto ao isolamento do ruído de impacto - Conrad, Liane Santos (2002)
The following research aims to verify the performance of various materials commonly used as floor coverings in the civil constructi on industry taking into consideration their capability to isolate impact noises. These materials have been compared and tests were carried out in the rooms of the Thermo acoustic Laboratory (LaTA) at the Federal University of Santa Maria, RS, Brazil (UFSM), with the purpose of measuring such impact noises, by following the specific ISSO 140/VII international regulations. The tests have also been conducted with rubber, synthetic materials, carpets of various densities, wooden laminates, both carpeted and not, with and without an isolating basis for carpets. The result analyses were attained by grouping the materials with similar characteristics. We have verified that the materials which showed better isolation of impact noises were not necessarily the thickest but the most resilient ones. The arousing data (results) from this research will be available to civil engineers as well as architects and might be of (their) use in design whenever acoustic comfort is aimed at.